2018
DOI: 10.1007/s11284-018-1570-8
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture and salt ionic composition effects on species distribution and diversity in semiarid inland saline habitats, northwestern China

Abstract: Salinization is one of the main types causing land desertification in arid and semi‐arid regions. Little is known about the impacts of salinization on the distribution and diversity of plant species, especially in semiarid inland saline habitats. We established a total of 40 sampling plots to determine plant community (floristic composition, species abundance, cover, frequency, and aboveground biomass) and soil characteristics (moisture, pH, electrical conductivity (EC), and the contents of Na+, K+, Ca2+, Mg2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Specimens previously reported by Li (2006) as Procypris rabaudi (Tchang, 1930) from Lake Dongting are possibly misidentified. This species is a rheophilic fish usually found in headwaters of rivers, but not in the lentic environment ( Zhang and Zhao 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specimens previously reported by Li (2006) as Procypris rabaudi (Tchang, 1930) from Lake Dongting are possibly misidentified. This species is a rheophilic fish usually found in headwaters of rivers, but not in the lentic environment ( Zhang and Zhao 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…To reflect changes in the composition of different communities, well-established diversity indexes were used in this study to represent species richness, evenness, dominance, community structure, and spatial heterogeneity (Whittaker and Niering, 1965 ; Zhang et al, 2018 ). We calculated them based on the species data obtained from the vegetation survey; the four specific indexes derived were as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Our data are consistent with the study by El-Ghani et al (2012), who reported that plant species diversity increases as soil moisture decreases. The dense canopy of tall-growing species along the water's edge makes germination and growth of other species more difficult, often leading to reduced species diversity (El-Ghani et al, 2012;Zhang et al, 2018).…”
Section: Effects Of Plant Species Diversity On Litter Decompositionmentioning
confidence: 99%